2020
DOI: 10.7717/peerj.9591
|View full text |Cite
|
Sign up to set email alerts
|

Regional distribution of Christensenellaceae and its associations with metabolic syndrome based on a population-level analysis

Abstract: The link between the gut microbiota and metabolic syndrome (MetS) has attracted widespread attention. Christensenellaceae was recently described as an important player in human health, while its distribution and relationship with MetS in Chinese population is still unknown. This study sought to observe the association between Christensenellaceae and metabolic indexes in a large sample of residents in South China. A total of 4,781 people from the GGMP project were included, and the fecal microbiota composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 54 publications
3
31
0
Order By: Relevance
“…The increased abundance of Akkermansiaceae may be considered a health-associated change after meat protein consumption because the level of Akkermansia muciniphila was shown to be positively correlated with the parameters involved in fatty acid oxidation and inversely associated with inflammatory markers and intestinal disorders, including inflammatory bowel disease [20] , [21] . Furthermore, the abundance of Christensenellaceae negatively correlated with the pathological features of obesity, hypertriglyceridemia, and body mass index [22] , and Akkermansiaceae and Christensenellaceae were both found to be the taxa of increasing abundance in the gut of centenarians [23] , [24] . In contrast, the abundance of Erysipelotrichaceae was shown to be positively linked to lipidemic imbalance and hypercholesterolemia and reported to be increased in patients with colorectal cancer [25] .…”
Section: Discussionmentioning
confidence: 97%
“…The increased abundance of Akkermansiaceae may be considered a health-associated change after meat protein consumption because the level of Akkermansia muciniphila was shown to be positively correlated with the parameters involved in fatty acid oxidation and inversely associated with inflammatory markers and intestinal disorders, including inflammatory bowel disease [20] , [21] . Furthermore, the abundance of Christensenellaceae negatively correlated with the pathological features of obesity, hypertriglyceridemia, and body mass index [22] , and Akkermansiaceae and Christensenellaceae were both found to be the taxa of increasing abundance in the gut of centenarians [23] , [24] . In contrast, the abundance of Erysipelotrichaceae was shown to be positively linked to lipidemic imbalance and hypercholesterolemia and reported to be increased in patients with colorectal cancer [25] .…”
Section: Discussionmentioning
confidence: 97%
“…C. minuta are sub-dominant Clostridiales species naturally present in the human gut of healthy individuals [ 28 ]. Because of their low abundance ranging from circa 0.2 to 2% of the gut microbiome, they tend to be overlooked in epidemiological studies, although a recent article established their prevalence to be around 50% in a Chinese cohort [ 6 ]. Nevertheless, the association between C. minuta and health has been largely documented [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, Christensenellaceae have been repeatedly associated with leanness in many observational population studies [ 3 , 4 , 5 , 6 ]. In addition, it has been shown that Christensenellaceae bacteria considerably increase during weight loss, suggesting a close relationship between the presence of these bacteria in the gut ecosystem and the regulation of energy metabolism [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found that a low fecal abundance of family Christensenellaceae at baseline may contribute to a high triglyceride or BMI after 24-week risperidone treatment for SZ. Despite that these associations cannot provide for causal pathophysiology; it has been suggested that abnormal Christensenellaceae may influence the lipid metabolism after risperidone treatment in patients[32].…”
Section: Discussionmentioning
confidence: 99%